Oxidative carbon-carbon bond formation - Keenlyside, M (2024)
Oxidative bond formation is a powerful technique for the efficient and atom-economic construction of carbon-carbon bonds. This thesis explores two systems that harness this reactivity to generate densely functionalised products. Initially, we describe an oxidative allylation discovered during a visible light eliminative photocyclisation. Investigation into the reaction mechanism determined that the cyclisation and oxidative allylation are two independent steps. However, the reaction is extremely substrate and nucleophile dependant, with limited tolerance for modification.